Nominal condensation in legal texts of the European Union - Honová, Zuzana (Romanica Olomucensia, 2014)
The article deals with the issue of nominal condensation, a characteristic feature of specialized discourse, and is based on legal texts of the EU institutions. It emphasises the specificity of legal texts as such and aims to compare the level of nominalisation in parallel French and Czech versions of judgements pronounced by the Court of Justice of the European Union. It tries to find the reason why the degree of nominalisation is also considerably high in Czech versions of these texts.
Keywords: nominal condensation; nominalisation; legal language; legislative discourse; specialized language; specialized text.